Road User Fees Instead of Fuel Taxes: The Quest for Political Acceptability. (21st March 2013) - Duncan, Denvil; Graham, John
<x xml:space="preserve">Abstract</x> In light of recent regulatory changes in federal fuel economy standards for cars and trucks, the consensus forecast is that motor fuel taxes will not be an adequate source of dedicated funding for roadway maintenance and construction. This article accepts the notion that mileage fees are a promising replacement for the fuel tax and considers steps that might be taken to enhance the political acceptability of such a reform. The authors argue that simple, low‐tech ways of implementing mileage fees are possible in the near term and should be complemented by a well‐developed audit mechanism. Current trends in the automotive and auto insurance industries as well as social media are likely to reduce opposition to more technologically advanced mileage taxes in the long run.